Effects of a moderate consumption of red wine on cardiovascular risk factors - Fernández Giusti, Alicia (2024)
Introduction: the cardiovascular illnesses will be among the main causes of death in Perú by the year 2020. Objective: to determine the effect of moderate consumption of red wine on some cardiovascular risk scores.Materials and methods: chromatography of anthocyanin and several polyphenols was used to measure wine antioxidant capacity. The selected volunteers, 14 men and 14 women, were distributed in 4 groups of 7; two groups drank wine for a month; biochemical tests were performed on all volunteers at days 0, 15 and 30.Results: the wine had 226.9 mg/L anthocyanins, C.I.50% of the free radical DPPH = 42.27 mg/mL; total polyphenols = 1281.57 mg/L; caffeic acid = 11.82 mg/L, quercetin = 9.40 mg/L and kaempherol =1.08 mg/L. In men wine reduced glucose levels significantly in 10.19%, VLDL in 10.79%; the coronary risk was reduced by15.97% in men and 36.5% in women; HDL levels were increased significantly, 19.98% in men and 55.15% in women.Conclusions: moderate consumption of red wine increased HDL levels and reduced the cardiovascular risk index, mainly in women.